Memory color effect induced by familiarity of brand logos. - Atsushi Kimura (Public Library of Science (PLoS), 2013)
Background When people are asked to adjust the color of familiar objects such as fruits until they appear achromatic, the subjective gray points of the objects are shifted away from the physical gray points in a direction opposite to the memory color (memory color effect). It is still unclear whether the discrepancy between memorized and actual colors of objects is dependent on the familiarity of the objects. Here, we conducted two experiments in order to examine the relationship between the degree of a subject's familiarity with objects and the degree of the memory color effect by using logographs of food and beverage companies. Methods and findings In Experiment 1, we measured the memory color effects of logos which varied in terms of their familiarity (high, middle, or low). Results demonstrate that the memory color effect occurs only in the high-familiarity condition, but not in the middle- and low-familiarity conditions. Furthermore, there is a positive correlation between the memory color effect and the actual number of domestic stores of the brand. In Experiment 2, we assessed the semantic association between logos and food/beverage names by using a semantic priming task to elucidate whether the memory color effect of logos relates to consumer brand cognition, and found that the semantic associations between logos and food/beverage names in the high-familiarity brands were stronger than those in the low-familiarity brands only when the logos were colored correctly, but not when they were appropriately or inappropriately colored, or achromatic. Conclusion The current results provide behavioral evidence of the relationship between the familiarity of objects and the memory color effect and suggest that the memory color effect increases with the familiarity of objects, albeit not constantly.